Tipping the Scales: The Migration–Selection Balance Leans toward Selection in Snake Venoms. (3rd November 2018) - Margres, Mark J; Patton, Austin; Wray, Kenneth P; Hassinger, Alyssa T B; Ward, Micaiah J; Lemmon, Emily Moriarty; Lemmon, Alan R; Rokyta, Darin R
Abstract: The migration–selection interaction is the strongest determinant of whether a beneficial allele increases in frequency within a population. Results of empirical studies examining the role of gene flow in an adaptive context, however, have largely been equivocal, with examples of opposing outcomes being repeatedly documented (e.g., local adaptation with high levels of gene flow vs. gene swamping). We compared neutral genomic and venom expression divergence for three sympatric pit vipers with differing ecologies to determine if and how migration–selection disequilibria result in local adaptation. We specifically tested whether neutral differentiation predicted phenotypic differentiation within an isolation-by-distance framework. The decoupling of neutral and phenotypic differentiation would indicate selection led to adaptive divergence irrespective of migration, whereas a significant relationship between neutral and venom expression differentiation would provide evidence in favor of the constraining force of gene flow. Neutral differentiation and geographic distance predicted phenotypic differentiation only in the generalist species, indicating that selection was the predominant mechanism in the migration–selection balance underlying adaptive venom evolution in both specialists. Dispersal is thought to be a stronger influence on genetic differentiation than specialization, but our results suggest the opposite. Greater specialization may lead to greater diversification rates, and extreme spatial and temporal variation in selective pressures can favor generalist phenotypes evolving under strong stabilizing selection. Our results are consistent with these expectations, suggesting that the equivocal findings of studies examining the role of gene flow in an adaptive context may be explained by ecological specialization theory.